Relationship between Lifestyle with Quality of Life in Breast Cancer Patients - Putri, Annisa Rahma Cahya; Ladesvita, Fiora; Burmanajaya, Bram (Universitas Muhammadiyah Surakarta, 2024)
The high rate of increase in mortality due to breast cancer shows the need for lifestyle modifications to reduce the mortality rate due to breast cancer. an increase in pain which results in a decrease in quality of life so that it can reduce compliance with patient treatment which hurts prognosis and death due to cancer. So it is important to target quality of life in breast cancer patients. Something closely related to a better quality of life is lifestyle, lifestyle modifications need to be made to maintain the lives of breast cancer patients. This research uses quantitative methods using a correlational design with a cross-sectional approach to determine the relationship between lifestyle and quality of life in breast cancer patients. Researchers used the pearson correlation test if the data is normally distributed (>0.05) and use the spearman correlation test if the data is not normally distributed (<0.05), this test is used to see whether there is a relationship between lifestyle and the quality of life of breast cancer patients. The research was conducted at the RSUD Kota Bogor with the total 116 respondents by filling in the Lifestyle Questionnaire Related to Cancer and the EORTC QLQ-30 quality of life instrument for breast cancer patients and the results of the two were correlated with a p-value <0.001, r = 0.88. Analysis of the relationship carried out on 8 lifestyle factors with 3 quality of life scales, was found that 5 lifestyle factors were interconnected with the quality of life scale. Overall, quality of life influences the lifestyle of breast cancer patients in Bogor City Regional Hospital with a strong positive relationship. This research can help clinicians in the development and management of cancer to improve the quality of life of breast cancer patients.